2017
DOI: 10.1016/j.healthplace.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The ward as emotional ecology: Adolescent experiences of managing mental health and distress in psychiatric inpatient settings

Abstract: Previous research on young people's satisfaction of inpatient services has often relied on the responses of carers and relevant practitioners. It is difficult to ascertain to what extent such reporting accurately represents the satisfaction levels of young people, with emerging research suggesting wide discrepancies. As part of a wider study evaluating the effectiveness of a Supported Discharge Service (SDS) operating within South London & Maudsley NHS Foundation Trust, this paper examines how young people exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 38 publications
0
47
0
9
Order By: Relevance
“…It seemed that when she wanted to be listened to, she was thoroughly questioned instead. As in Reavey et el's research, which looked at experiences in inpatient care, Ali seemed to quickly pick up on the unyielding emphasis on risk management within hospitals, and also felt that her emotions needed to be contained within those settings (25). With regard to crisis services, which she intensely disliked, the clubhouse offered her a preferred solution.…”
Section: Findings [A] How I Experience the Clubhouse Compared With Homentioning
confidence: 97%
See 1 more Smart Citation
“…It seemed that when she wanted to be listened to, she was thoroughly questioned instead. As in Reavey et el's research, which looked at experiences in inpatient care, Ali seemed to quickly pick up on the unyielding emphasis on risk management within hospitals, and also felt that her emotions needed to be contained within those settings (25). With regard to crisis services, which she intensely disliked, the clubhouse offered her a preferred solution.…”
Section: Findings [A] How I Experience the Clubhouse Compared With Homentioning
confidence: 97%
“…Norman conducted a qualitative study in which three main thematic items were identified: meaningful relationships, important work tasks and a supportive environment. Reavey and colleagues (25) conducted research regarding inpatient experiences within a Supported Discharge Service in a London borough, making it very valuable in terms of comparison and context. Young people described hospital wards as places to contain behaviour, rather than as places to treat and deeply explore mental health difficulties.…”
Section: Relevant Qualitative Research [A]mentioning
confidence: 99%
“…Content analysis has been shown to be a relevant and effective qualitative research methodology in the field of nursing, as a systematic means of describing phenomena and establishing relational links between concepts. Inductive methods of content analysis in which data is analysed through a theoretical lens to support understanding and meaning-making are particularly indicated to build up a conceptual system or enhance understanding when there is insufficient pre-existing knowledge of the issue (Elo & Kyngäs 2007;Reavey et al 2017). The study was conducted in one 10-bed mixed gender CAMHS PICU in the North of England.…”
Section: Designmentioning
confidence: 99%
“…These issues heighten with adolescents, who owing to their developmental stage value their autonomy, but are now in a position of even tighter adult controls. In discussing hospitalizations, adolescents told researchers that when the unit focus is limit setting on overt behaviors, staff often fail to see and respond to their underlying distress (Reavey et al., ). Thus, an element of support is the balance staff reaches between their need to maintain control over the tone and pace of the milieu and adolescents’ need for autonomy.…”
Section: Supportmentioning
confidence: 99%